Effectiveness of a smoking restriction policy on smoking behaviour in the military. (April 2017) - Chiu, Yu-Lung; Lo, Hsin-Chun; Lai, Ching-Huang; Hwang, Shu-Ling; Lin, Fu-Gong; Huang, Shu-Jia; Jiang, Shiang-Huei; Li, Shan-Ru; Tzeng, Ya-Mei; Fang, Wen-Hui; Kao, Senyeong
Highlights: Active and regular restriction policies in the military were evaluated. The change of smoking behaviours was assessed during basic recruit training. 867 and 840 conscripts under the active and regular restriction policies were observed. Active smoking restrictions could reduce the daily cigarette consumption of smokers. Smokers under the active smoking restrictions decrease nicotine dependence.